TENAGA KERJA SEKTOR FORMAL DAN INFORMAL DI KABUPATEN BANGKALAN - Yustina - Chrismardani; Bondan Satriawan (MediaTrend, 2018)
One of the interesting things studied from Kabupaten Bangkalan is the aspect of employment, especially based on formal and informal sector. Based on the formal sector workers who belong to the category of workers / workers and tried to be assisted by permanent workers / workers paid up to 76 percent, and informal workers are who try their own, trying to be assisted by temporary workers, free workers in agriculture, free workers in non-paid to reach 24 percent. Other important findings indicate that there is no significant difference in the total income of workers in the formal and formal sectors, which is an average of Rp 76,184, and it turns out that Bangkalan regency has not been the target of workers migration from the surrounding area.